Recyklace - Mitana, Mikuláš (Vysoké učení technické v Brně. Fakulta výtvarných umění, 2024)
Záměrem bakalářské práce je především poukázání na přebytek materiálu a zahlcování planety odpady, možnosti recyklace pevných materiálů, jako je například kov, a přetavení do jiných předmětů. Zásadní je nejen práce s materiálem, ale i s lidmi uvnitř kovošrotu. Vytvoření sociálního kontaktu s pracovníky a spolupráce na přetvoření odpadu do podoby sochařských děl a vytvoření videa je pro bakalářskou práci zásadní.

The intention of the bachelor thesis is mainly to highlight the surplus of materials and the overwhelming of the planet with waste, the possibilities of recycling solid materials such as metal and remelting them into other objects. Working not only with the material but also with the people inside the scrap metal is essential. Creating a social contact with the workers and working together to transform the waste into sculptural works and create a video is essential for the bachelor thesis.
Recycling
Keywords: Kovošrot; odpad; kov; recyklace; antropocén; spolupráce; sociální kontakt; pracovníci; video; dokument; dočasnost; sochy; ne-sochy; Metal scrap; waste; metal; recycling; anthropocene; cooperation; social contact; workers; video; documentary; temporality; sculptures; non-sculptures